Occupational therapy combined with computerized cognitive remediation therapy for the treatment of early-onset Alzheimer's disease： a case report - Liu Xiaowei; Fan Wei; Wang Ziqi; Cai Qingyan (Sichuan jingshen weisheng)
This paper reported a patient with early-onset Alzheimer's disease （AD） who had previously responded poorly to anti-dementia medications while showed improvement in cognitive functioning after treatment with occupational therapy and computerized cognitive remediation therapy （CCRT） for 50 minutes three times per week. This case report provided an in-depth evaluation of occupational therapy combined with CCRT for early-onset AD in an effort to inform cognitive rehabilitation of patients with AD. ［Funded by Chengdu Medical Scientific Research Project （number， 2023635）］